1992
DOI: 10.1021/cm00021a011
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vapor deposition precursor chemistry. 3. Formation and characterization of crystalline nickel boride thin films from the cluster-assisted deposition of polyhedral borane compounds

Abstract: compounds and to elucidate the important factors for determining the suitability of a source compound for the formation of desirable thin film materials. Acknowledgment. We thank Dr.The deposition of both metal-rich and boron-rich thin-film phases of nickel boride from boron-containing precursor compounds by a cluster deposition process is reported. The thin films were characterized by EDXA, AES, SEM, XRD, FT-IR, TEM, and electron diffraction experiments. The films were shown by AES to be compositionally unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 1 publication
2
18
0
Order By: Relevance
“…Appropriate care was taken in handling the boron hydrides under inert atmosphere conditions. [25,26] The anhydrous (99.9%) neodymium(III) chloride (NdCl 3 ) and cobalt(II) chloride (CoCl 2 ) were purchased form Cerac Inc. and were used as received and always handled under an inert atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Appropriate care was taken in handling the boron hydrides under inert atmosphere conditions. [25,26] The anhydrous (99.9%) neodymium(III) chloride (NdCl 3 ) and cobalt(II) chloride (CoCl 2 ) were purchased form Cerac Inc. and were used as received and always handled under an inert atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…[25] A quartz reactor tube apparatus (1 × 10 −6 Torr ultimate vacuum) was used which employed a 10 mm (o.d.) tube with an overall length of 60 cm.…”
Section: Chemical Vapor Deposition Of Neodymium Boridementioning
confidence: 99%
See 2 more Smart Citations
“…Wodnieka et al crystallized amorphous Nickel-boride alloys and observed a side product in the final yield [3]. A similar behavior was seen when thin films of Ni 3 B were synthesized by chemical vapor deposition method [4] or during the crystallization of Nickel-Boron metallic glasses [5]. Machizaud et al studied an amorphous alloy, Ni 66 B 34 , and postulated that Ni 7 B 3 decomposes above 500°C to form Ni 3 B and Ni 2 B [6].…”
Section: Introductionmentioning
confidence: 82%